PARAMETERS ON SUPPORT STRUCTURE DESIGN FOR METAL ADDITIVE MANUFACTURING. (May 2020) - Weber, S.; Montero, J.; Bleckmann, M.; Paetzold, K.
Abstract: The topic of support structure design in the Design for Additive Manufacturing (DfAM) field is not addressed with the same relevance as the topic of part design. Therefore, this contribution investigates parameters for both the manufacturing and support structure design for the Laser Powder Bed Fusion (L-PBF) process. Matrices for cause-effect-relations of manufacturing and design parameters on build properties as well as correlations of them are presented. Based on these, recommendations for actions for experimental procedures are derived following the Design of Experiments method.